FORMATION OF PALM OIL CULTIVATION IN PARA’S AMAZON - João Santos Nahum (Mercator - Revista de Geografia da UFC, 2020)
The formation of palm oil cultivation in Para’s Amazon has as guide the state action. Emphasizing that the state makes possible the arrival of palm oil, encourages business creation through programs, projects and policies. The process of reconstituting milestones on origin, consolidation and expansion, which goes from the 1950s to the second decade of the 21st century, was based on the vast literature review on the topic, data collection about palm oil cultivation, palm oil production, emergence, merger, business extinction and the situation of family farming integration projects. Th first part of the text focus on the arrival of oil palm in the Amazon, next, has highlight the creation of palm oil companies and finally analyze palm oil policies. This explains the distribution of the crop predominantly by the Tomé-açu microregion and the current period marked by the projects of integration of rural farmers into the palm oil agribusiness chain, through the discourse of rural territorial development with social inclusion, and job and income generation.